Green Management Practices and Competitive Advantage among Small and Medium Enterprises in The Gambia: A Qualitative Study - Lamin Saidyjeng; Issa G. Ahmed; Abubakar Muhammad Jibril (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This paper aims to examine the green management practices adopted by small and medium enterprises (SMEs) in The Gambia and to analyze how these practices contribute to competitive advantage within a resource-constrained economic context.Method: The study employs a qualitative documentary approach based on the analysis of secondary data drawn from government policies, reports issued by international agencies, and SME-related publications produced between 2018 and 2025. The data were analyzed using thematic analysis, guided by the Resource-Based View and Institutional Theory.Result: The findings reveal several common, although largely informal, green management practices among SMEs, primarily focused on energy conservation, basic waste management, and resource protection. These practices are predominantly cost-driven and reactive in nature. Nevertheless, they generate competitive advantages by lowering operational costs, strengthening organizational legitimacy, and enhancing business resilience. Their wider adoption, however, is constrained by limited financial capacity, weak regulatory enforcement, and insufficient strategic managerial awareness.Practical Implications for Economic Growth and Development: The findings indicate that integrating sustainability into SME capacity-building programs is essential for strengthening long-term competitiveness and promoting employment generation. Policymakers and development partners should therefore reposition green practices as strategic investments in resilience by supporting them through financial incentives, practical implementation tools, and targeted training initiatives.Originality/Value: This study provides one of the earliest firm-level qualitative examinations of the strategic adoption of green management practices by SMEs in The Gambia. In doing so, it addresses an important gap in the sustainability literature concerning small African economies.